Identification of root causes of construction and demolition (C&D) waste: the case of Turkey - Polat, Gul; Damci, Atilla; Turkoglu, Harun; Gurgun, Asli Pelin (ELSEVIER SCIENCE BV, 2017)
Construction and demolition (C&D) waste is defined as the waste produced during new construction, renovation, and demolition of buildings and structures. C&D waste is becoming one of the most serious environmental problems. Indeed, recent studies reveal that C&D waste constitutes approximately 10-30% of the waste received at many landfill sites around the world. In the literature, there are numerous studies focusing on C&D waste in the construction industry. These studies can be categorized into three main groups, which are; the studies that attempt to identify the root causes of waste generation, the studies that deal with the estimation and management of C&D waste, and the studies that concentrate on the prevention and reduction of waste generation. This study aims to identify the importance levels of the root causes of material waste during new construction in the Turkish construction industry. For this purpose, an extensive literature review on construction waste was carried out, 34 waste causes were identified, and a questionnaire that consists of 41 questions was designed. These questionnaires were sent to 66 contractors. Reliability and ranking analyses were performed on the collected data in order to understand the importance levels of these waste causes. It was found that frequent design changes and change orders, design and construction detail errors, and waste from cutting uneconomical shapes have High importance level for C&D waste generation, and none of these 34 factors has Medium-Low or Low importance level. (C) 2017 The Authors. Published by Elsevier Ltd.
Keywords: Construction and demolition (C&D) waste; root causes; questionnaire; Turkey; MINIMIZATION; GENERATION; Construction & Building Technology; Engineering